PENCIPTAAN BUKU ESAI FOTOGRAFI GREBEG BESAR YOGYAKARTA SEBAGAI UPAYA MEMPOPULERKAN FILOSOFI BUDAYA JAWA - Kresnadana, Dony Bagus; Fianto, Achmad Yanu Alif; Sutikno, Sutikno (Jurnal Art Nouveau, 2015)
Abstract: Grebeg Besar ceremony of alms form Earth in the shape of a mount that contains results that are in the city of Yogyakarta. This Grebeg Besar ceremony was held on the 10th Dzulhijjah or coinciding with the feast of Eid al-Adha. The ceremony is already very well known in the Yogyakarta region a lot of media who already publish the ceremony but from various media no one tells the story and review in detail about the ceremony of the Grebeg Besar. But behind it all, there is an awful lot of value philosophy and philosophy is still waking up to this point. As the effort so that the values of an existing philosophy at the ceremony is known by the public, then it will be made of the creation of a book containing the photo essay about the procession Grebeg Besar ceremony in an effort to popularize philosophy of culture. Research methods qualitative method is done by conducting interviews, observation, documentation, library and study to get the data used as the supporter of the creation of the concept of the creation of a book of photo essay. Analysis of the data done then found keyword "Offerings the leader". then the keyword will be applied to this photo essay book so that the contents of the book describes a King who generously gave alms to the people. The result of the creation of this photo essay book is to popularize return values the philosophy contained on a giant Big Ceremony.Â Keywords: Photography Essay Book, Ceremony Grebeg Besar, Yogyakarta, philosophy of Culture